2016
DOI: 10.2495/eid160121
|View full text |Cite
|
Sign up to set email alerts
|

Assessing gaseous pollutants and air quality in some areas of Kano metropolis, Kano, Nigeria

Abstract: This study assesses the air quality of some areas in Kano metropolis. It was conducted for a period of two months in 2013 through direct field measurement of gaseous pollutant concentration in ten different locations using mobile gas censors. The air pollutants measured includes carbon monoxide (CO), sulphur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), hydrogen sulphide (H 2 S), methane (CH 4 ) and ammonia (NH 3 ). In some areas, the study indicated higher concentrations of CO, NO 2 and H 2 S above the air quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This trend could be attributed to lower vehicular movement around these areas in comparison to the industrial and commercial areas visited in this study. Olayinka et al (2015) and Garba and Yunusa, (2016) reported that the source of outdoor airborne gaseous pollutants in Abeokuta and Kano metropolis, North Central Nigeria was vehicular exhaust emissions and observed high concentrations of these pollutants in municipal areas where the vehicular traffic was also high. The values of the gaseous pollutants observed at Kuto and Panseke in this study contrasted with seasonal values reported by Olayinka et al (2015).…”
Section: Fig 3: Mean Noise Concentrations For the Commercial Locationsmentioning
confidence: 99%
See 3 more Smart Citations
“…This trend could be attributed to lower vehicular movement around these areas in comparison to the industrial and commercial areas visited in this study. Olayinka et al (2015) and Garba and Yunusa, (2016) reported that the source of outdoor airborne gaseous pollutants in Abeokuta and Kano metropolis, North Central Nigeria was vehicular exhaust emissions and observed high concentrations of these pollutants in municipal areas where the vehicular traffic was also high. The values of the gaseous pollutants observed at Kuto and Panseke in this study contrasted with seasonal values reported by Olayinka et al (2015).…”
Section: Fig 3: Mean Noise Concentrations For the Commercial Locationsmentioning
confidence: 99%
“…Several prevalent air pollutants in urbanized areas include; dioxides of sulphur and nitrogen; (SO2) and (NO2), carbon (II) oxide (CO), volatile organic compounds (VOCs), hydrogen sulphide (H2S), suspended particulate matter (SPM) with aerodynamic diameters under 2.5 and 10µm, lead (Pb) and ozone (O3) (Garba and Yunusa, 2016;Ipeaiyeda and Adegboyega, 2017;Njoku et al, 2018;Nwosisi et al, 2021). These air pollutants have been described as criteria contaminants as they are strongly suspected to have negative health effects on both humans and the biotic and abiotic components of the environment (Ipeaiyeda and Adegboyega, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CO background concentration in troposphere in non-urban, unpolluted areas usually spans in the parts-per-million (ppm) range [2] , [3] , as recently confirmed by the data collected in the Measurements of Pollution in the Troposphere (MOPITT) NASA mission [4] . Nevertheless, these values may grow up to ppm in urban or metropolitan areas because of vehicles exhaust or industrial emissions [5] , [6] . In closed environments (such as houses or offices), carbon monoxide may reach the worrying concentrations of ppm due to indoor fires, depending on ventilation condition of the room [7] .…”
Section: Introductionmentioning
confidence: 99%